Segmentasi, Penentuan Target dan Posisi Pasar Serta Bauran Pemasaran Produk layanan Skrining Covid-19 di RSIA Cinta Kasih - Lovia Lova (Jurnal Medika Hutama, 2022)
Background: Currently, people are expected to coexist with covid-19. COVID-19 screening is an early detection testing strategy to identify cases. Early detection is one of the ways to prevent the rapid spread of this disease and is also important for patients to be quickly handled and avoid more severe symptoms. Therefore RSIA Cinta kasih set to make covid-19 screening test service products. In order to be able to compete with other hospitals which provide the same service product. Purpose: kowing how RSIA implemented segmentation, targetting, positioning and marketing mix of this Covid-19 screening test service product as a marketing strategic Methode: This research uses qualitative descriptive method, data obtained based on interviews with the head of marketing, observation of activities from covid screening and review of related documents. The results showed that RSIA Cinta Kasih has done segmentation, targetting and positioning and marketing mix well. Currently 70% of patients who conduct covid-19 screening tests know about this service product through online promotion. Keywords: segmentation; targetting; positioning; marketing mix; service product